Molecular-genetic and cytogenetic analyses of cotton chromosome introgression from Gossypium barbadense L. into the genome of G. hirsutum L. in BC2F1 hybrids - M. F. Sanamyan; Sh. U. Bobokhujayev; Sh. S. Abdukarimov; O. G. Silkova (Вавиловский журнал генетики и селекции)
Substitution lines of the cotton Gossypium hirsutum L. involving chromosomes of the tetraploid species G. bar ba dense L., G. tomentosum Nutt. ex Seem., and G. mustelinum Miers ex Watt. are a valuable source for breeding, increasing the genetic diversity of G. hirsutum. The substitution of certain G. hirsutum L. chromosomes with G. barbadense chromosomes affect fibre elongation, fibre yield, fibre strength, and micronaire. To increase the efficiency of creating lines, it is necessary to study the nature of the introgression of alien chromosomes into the G. hirsutum L. genome. As a result of molecular genetic analysis of BC2F1 hybrids obtained from crossing monosomic lines of the cotton G. hirsutum from the cytogenetic collection of Uzbekistan with monosomic backcross hybrids BC1F1 G. hirsutum × G. barbadense on the same chromosomes, genetic differences between the hybrids in the profile of chromosome-specific microsatellite SSR markers were found. The predominant introgression of chromosomes 4, 6 and 12 of the At-subgenome and 22 of the Dt-subgenome of G. barbadense was revealed, while chromosomes 2 and 7 of the At-subgenome and 18 of the Dt- subgenome of G. barbadense were characterized by elimination. Among them, chromosomes 7 of the At- sub genome and 18 of the Dt-subgenome of G. barbadense were eliminated in the first backcross generation. In this work, two lines, CS- B06 and CS-B07, from the American cytogenetic collection with a putative substitution involving chromosomes 6 and 7 of the At-subgenome were analysed. The presence of only polymorphic alleles from the species G. hirsutum and the absence of polymorphic alleles from the species G. barbadense were revealed, which showed the absence of substitution involving these chromosomes. BC2F1 hybrids with monosomy for both G. barbadense and G. hirsutum chromosomes were characterized by regular pairing of chromosomes and high meiotic indexes. However, many hybrids were characterized by a decrease in pollen fertility. Two hybrids with monosomy for chromosome 7 of the At-subgenome of G. hirsutum and chromosome 6 of the At-subgenome of G. barbadense had the greatest reduction in pollen viability (70.09 ± 1.57 and 75.00 ± 1.66 %, respectively). Thus, this work shows a specific feature in the introgression of individual chromosomes of the cotton species G. barbadense into the cotton G. hirsutum genome.